2017
DOI: 10.1097/pr9.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Persistent postsurgical pain in children and young people: prediction, prevention, and management

Abstract: Ensuring optimum preoperative and postoperative pain management should always be a priority in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(89 citation statements)
references
References 49 publications
2
87
0
Order By: Relevance
“…Acute postsurgical pain has been shown to predict chronic pain and opioid use in children and adolescents [6,7]. Moreover, the persistent nature of postoperative pain may delay rehabilitation [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Acute postsurgical pain has been shown to predict chronic pain and opioid use in children and adolescents [6,7]. Moreover, the persistent nature of postoperative pain may delay rehabilitation [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…In response to a postal questionnaire survey to determine the prevalence of chronic pain in children who had undergone cardiac surgery with sternotomy, Lauridsen found the risk although low is not negligible and may have an associated neuropathic component. Hence, optimum perioperative management of pain should be a priority to decrease the occurrence of chronic pain …”
Section: Introductionmentioning
confidence: 99%
“…Hence, optimum perioperative management of pain should be a priority to decrease the occurrence of chronic pain. 15 One way to overcome this problem is the use of local anesthetic techniques. These techniques can block afferent impulses from corresponding nerves and thereby either reduce the need for opioids or eliminate them completely.…”
mentioning
confidence: 99%
“…If clinicians do ask patients about pain-related affective or evaluative dimensions, it is currently more art than science as to how they then integrate and respond to this information alongside other physiological and behavioral pain indicators and management protocols. It has been suggested that clinician acute pain treatment decisions are typically based on the presumed mechanism of the pain, previous pain medication use, and clinician experience [3], and there has been little, if any, attention devoted to how best to integrate functional measures, behavioral observations, and children's self-report with such factors. One study found that clinician estimations of a child's procedural pain intensity were influenced by the child's diagnosis, the child's pain behaviors and the clinician's own distress in the anticipatory phase, with higher clinician distress predictive of greater subsequent pain intensity ratings [64].…”
Section: Multidimensional Pain Assessment and Therapeutic Decision-mamentioning
confidence: 99%
“…Acute pain may be taken to include all painful experiences lasting for less than 3 months duration [1]. A thorough acute pain assessment should be conducted within a broader social and developmental perspective, considering information from various sources, which may include self-reported information, behavioral observations, physiological measures, parent-or clinician-reported information, and the patient's medical history [2], complemented by an understanding of pain mechanisms and pathophysiology [3]. Each of these assessment modalities may provide valuable information about the pain experience.…”
Section: Introductionmentioning
confidence: 99%